'We can't do that here': negotiating evidence in HIV prevention campaigns in southwest China. Issue 2 (15th March 2017) - Uretsky, Elanah
Abstract: Disease prevention and health care delivery, areas traditionally governed by the nation state and local communities, are increasingly being inhabited by 'mobile sovereigns' who carry a global currency of prevention strategies and treatments grounded in the universal standards of scientific evidence. Drawing on ethnographic evidence from research conducted on HIV in southwest China, this paper examines the impact of evidence-based science on the effectiveness of global health programming. It interrogates the intentions of global health partnerships and how the balance of power waged between those with money, science, and technical expertise, and those seeking assistance and resources, influences global health programming. Ultimately, the paper demonstrates the disconnect between the demand for a system of universal standards developed on the basis of scientific evidence and an appreciation for the local context, which shapes the way these standards should be modified for effective implementation of global health programs.